Comparative Analysis of the Results of Mine Surveying and Numerical Studies of the Running Tunnel of the Kyiv Metro - Bondarenko, N. K; Tiutkin, O. L (Science and Transport Progress, 2022)
Purpose. The article is aimed to perform a comparative analysis of the results of mine surveying and numerical studies of the running tunnel of the Kyiv metro and obtain the reliability of the author’s system of parametric analysis. Methodology. The comparative analysis of the results of research on the displacements of the running tunnel was carried out in two directions. In the first direction, the movement of the lining of the running tunnels between the stations «Slavutych» – «Osokorky», «Osokorky» – «Pozniaky» and «Pozniaky» – «Kharkivska» obtained in the course of mine surveying studies was analyzed. In the second direction, a numerical analysis using the finite element method was performed. For this analysis, models of three lining rings were created. These rings were chosen because the maximum level of vertical movements was observed in them. Their reason is the influence of the engineering and geological conditions of the part of the Syretsko-Pecherska line on the left bank of the Dnipro River. These conditions are characterized by the layering of weak and water-saturated soils (sands of various sizes and densities, sandy loams, light loams and clays). The lining of the real tunnel is a standard structure used for shield tunneling of the Kyiv metro. The models reflect the geometric dimensions of the running tunnels, as well as the deformation characteristics and soil density of the surrounding layered massif. Findings. The authors analyzed the characteristics of the layered massif and the maximum displacements of the running tunnels of the part of the Syretsko-Pecherska line on the left bank of the Dnipro River. In the course of the numerical analysis, the vertical displacements of the models of the three lining rings were obtained. A comparative analysis of the results of mine surveying and numerical studies was carried out. The obtained level of error (up to 15 %) between the results of mine surveying and numerical studies proves that the developed bases of parametric analysis are reliable. Originality. For the first time, the theoretical foundations of parametric analysis for a real underground object were introduced. The author’s developments related to the creation of finite-element models based on the real characteristics of the soils of the layered massif provide a high level of similarity to the results of theoretical developments and instrumental mine surveying measurements. Practical value. It consists in the substantiation of the parameters of the deformed state that occurs in the horizontal working during shield tunneling.